Pharmacoeconomic analysis of blood glucose meter Contour TS in diabetes treatment - A. U. Kulikov; V. V. Babiy (Фармакоэкономика)
approximately 5-7% of people in Russia have diabetes. In addition, the number is growing every year. Diabetes treatment schemes mostly focused on normalizing the blood glucose level. To achieve it patients use the glucose meters. However, there are some technique differences between meters that could influence on the cost and effectiveness of diabetes and its complications treatment. This pharmacoeconomic research compared the cost-effectiveness and the budget impact results of using Contour TS, Accu-Chek Active and OneTouch Select. Research outcomes demonstrate the pharmacoeconomic advantages of using Contour TS as blood glucose meter in diabetes treatment schemes.